Subterranean statecraft: Invisible diplomacy in Australia's external relations. Issue 127 (December 2021) - Fernandes, Clinton
Abstract: This paper examines three sites where diplomacy interacts with geoscience, international law, and military capabilities. These sites, invisible to the general public due to their subterranean character, are undersea long-distance telecommunications cables; submarine operations; and espionage operations. The paper uses these subterranean sites to shed light on the hidden dimensions of Australian statecraft. Taken as a whole, they illustrate the influence of elite economic interests in Australia's national security objectives. The covert instruments of statecraft are devoted not just to military security but to the power and interests of the private sector. These interests heavily influence the concept of "national interest" in Australia's external relations.